Base of Articulation of 13 Indian Languages - Savithri S.R.; Jayaram M; Venugopal M.B.; Rajasudhakar R (Journal of All India Institute of Speech and Hearing, 2007)
Honikman (1964) defined base-of-articulation of a language as an articulatory setting that reflects the settings of the most frequently occurring segments and segmental combinations in the language. The present study investigated the nature of cross-language differences in base-of-articulation in 13 Indian languages namely, Assamese, Bengali, Hindi, Kannada, Kashmiri, Kodava, Oriya, Rajasthani, Malayalam, Marathi, Tamil, Telugu, and Punjabi that have phonemically unequal vowel inventories. Five males and five females speaking each language participated in the study. Non-sense V1CV2 syllables were recorded from ten normal native speakers in each of the 13 languages. Frequencies of the first and second formants were measured using CSL 4500. The five common vowels existing in all languages were compared for base-ofarticulation. Difference. Results indicated significant difference between languages, vowels, and gender. In brief, F1 was high in Oriya and Marathi, and was low in Bengali, Punjabi and Kannada; others were in between. Prominently base-of-articulation (position of tongue, F2) is fronted in Bengali, is back in Kashmiri and other Indian languages are in between. The results of the present study have augmented the knowledge about cross-language differences in base-of-articulation in Indian languages. Also, the results help in rehabilitation process.